A drug safety evaluation of apixaban for the treatment of atrial fibrillation, acute coronary syndrome, and percutaneous coronary intervention. Issue 12 (2nd December 2019) - Gumprecht, Jakub; Domek, Magdalena; Lip, Gregory Y. H.
ABSTRACT: Introduction : The non-vitamin K antagonist oral anticoagulants (NOACs) are changing the landscape for stroke prevention in atrial fibrillation (AF) and prevention or treatment of venous thromboembolism (VTE). In patients with AF and concomitant acute coronary syndrome (ACS), the treatment regimen of combined NOACs and P2Y12 inhibitors is gaining popularity. Areas covered : We conducted a review of safety evaluation and effectiveness of apixaban for AF and ACS treatment, both alone and in combination with different antiplatelet treatment regimens. The aim was to provide an overview of apixaban including mechanism of action, indications, adverse events and tolerability. Expert opinion : Apixaban is recommended as a safe, well tolerated and effective oral anticoagulant for reducing the risk of ischemic events among AF patients. It is of value in prevention and treatment of VTE and pulmonary embolism. Comparing to VKA, apixaban was superior in preventing stroke or systemic embolism with lower major bleeding events among AF patients. When combined with dual antiplatelet therapy apixaban may cause dose-related increase in bleeding which reduces the benefit of this treatment regimen among ACS patients but without AF. In those with ACS and concomitant AF, the combination of apixaban with P2Y12 inhibitor appears to be safe and effective.